HECT Domain-containing E3 Ubiquitin Ligase Nedd4 Interacts with and Ubiquitinates Sprouty2 - Edwin, Francis (American Society for Biochemistry and Molecular Biology, 2010)
Sprouty (Spry) proteins are important regulators of receptor tyrosine kinase signaling in development and disease. Alterations in cellular Spry content have been associated with certain forms of cancers and also in cardiovascular diseases. Thus, understanding the mechanisms that regulate cellular Spry levels are important. Herein, we demonstrate that Spry1 and Spry2, but not Spry3 or Spry4, associate with the HECT domain family E3 ubiquitin ligase, Nedd4. The Spry2/Nedd4 association involves the WW domains of Nedd4 and requires phosphorylation of the Mnk2 kinase sites, Ser(112) and Ser(121), on Spry2. The phospho-Ser(112/121) region on Spry2 that binds WW domains of Nedd4 is a novel non-canonical WW domain binding region that does not contain Pro residues after phospho-Ser. Endogenous and overexpressed Nedd4 polyubiquitinate Spry2 via Lys(48) on ubiquitin and decrease its stability. Silencing of endogenous Nedd4 increased the cellular Spry2 content and attenuated fibroblast growth factor-elicited ERK1/2 activation that was reversed when elevations in Spry2 levels were prevented by Spry2-specific small interfering RNA. Mnk2 silencing decreased Spry2-Nedd4 interactions and also augmented the ability of Spry2 to inhibit fibroblast growth factor signaling. This is the first report demonstrating the regulation of cellular Spry content and its ability to modulate receptor tyrosine kinase signaling by a HECT domain-containing E3 ubiquitin ligase.